Active methodologies in the professional master's degree in health education: expanding the spaces for knowledge construction (Research, Society and Development, 2020)
This article aims to reflect on the theoretical contents and practices carried out with the use of active methodologies in a discipline of the Professional Master in Health Education (MPES), as well as on the impact of these methodologies in the construction of knowledge, bringing the universe closer professional and the gym. This is an experience report, with a qualitative approach, which brings the experiences of the first author in the classes of Theoretical-Philosophical Concepts and Teaching Practices, at the MPES of the Aurora de Afonso Costa School of Nursing/Universidade Federal Fluminense, in the year 2019. This discipline had the challenge of leading the master's students of technical and compartmentalized thinking of their daily activities to the academic universe, using authors such as Freire, Berbel, Bachelard, Pedro Demo, Fazenda and Perrenoud, which made it possible to approach philosophical thinking with the practice of health professionals. It is noteworthy that the reading of theorists and the methodology used enabled the critical and reflective analysis of professional practices, in addition, the confrontation of different authors, actors and sources favored the sharing of scientific knowledge and a new professional posture, bringing the academy closer to services . It is considered that there is a good way to go, but these small changes must be valued, after all, when used in the professional master's degree, they make it possible to qualify teaching, research and assistance.